Authorities and Responsibilities of Notaries as Officials Cooperative Establishment Deed Maker - Muhammad Yusrizal; Surya Perdana; Triono Eddy (DE LEGA LATA: JURNAL ILMU HUKUM, 2022)
Cooperative is a business entity established by and consisting of individuals. The purpose of establishing a Cooperative is as a joint effort based on the principles of kinship and democracy, which in turn requires a strong legal basis relating to the deed of establishment of a Cooperative using an authentic deed. Considering the need for a Notary in the growth and development of Cooperatives as a legal entity, especially in the process of its establishment and amendments to its articles of association, then based on the State Decree of Cooperatives and Small and Medium Enterprises Number: 98/KEP/M.UKM/IX/2004, Notaries are given the authority to make Cooperative deed. Notary authority is very important, namely as a public official authorized to make authentic deeds and other authorities as referred to in Law Number 30 of 2004 concerning Notary Positions. The involvement of a notary is not only to assist the process of making cooperative deeds, but also to care about the prospects for the development of cooperatives that are clients and are willing to provide legal guidance and consultation related to the making of cooperative deeds. The goal is that the cooperative movement and the cooperative community understand more and are not unfamiliar with matters related to the rule of law